Entrepreneurial networking and creativity: A practice perspective on the collaboration between start-ups and intermediaries - Thomas Schmidt; Braun, T.; Ferreira, A. (2015 European Academy of Management Conference: Uncertainty is a great opportunity, 2015)
To shed light on the dynamics between networks and creativity, we propose to examine entrepreneurial networking as initiated and maintained by organizationally embedded practices. This allows us to shift the focus from the individual entrepreneur to the entrepreneurial firm with its executives and employees. In a survey-based study, drawing from the data of 101 CEOs and 261 employees in start-ups, multilevel moderated mediation analysis is applied. According to our results, interorganizational relationships are particularly effective for organizational creativity if networking practices are in place. Herein, the involvement of employees from lower hierarchical levels turned out to have a stronger mediation effect than the individual efforts by the CEO. These findings support a “post-heroic” perspective that is quite distinctive from previous entrepreneurship research, which predominantly captures networking as an individual activity of a luminary entrepreneur.